Oral health-related quality of life among pediatric liver transplant candidates - Evelyn Alvarez VIDIGAL; Jenny ABANTO; Ana Estela HADDAD; Gilda PORTA; Fábio Abreu ALVES; Marcelo BÖNECKER (Brazilian Oral Research, 2020)
Abstract To assess the impact of oral conditions on the oral health-related quality of life (OHRQoL) of pediatric liver transplant candidates. This cross-sectional study included 60 children aged 13 to 48 months who were liver transplant candidates that attended the AC Camargo Cancer Center, São Paulo, Brazil. On the day of oral examinations, the children’s mothers were invited to answer two questionnaires; one related to children’s OHRQoL using the B-ECOHIS and another related to socioeconomic/demographic characteristics. Thereafter, a single, adequately trained dentist carried out children’s oral examinations for gingival inflammation (Silness-Löe index), dental plaque (Green-Vermillion Simplified index), dental caries (dmft index), developmental defects of enamel (DDE index), tooth discoloration, oral mucosal/lip alterations. The data collected also included socioeconomic/demographic characteristics and liver disease. The adjusted Poisson regression model was used to associate children’s socioeconomic/demographic characteristics and clinical conditions to the outcome. The adjusted regression model showed that children with untreated caries lesions (RR = 3.35, p < 0.0001) and tooth discoloration (RR = 1.74, p = 0.04) had poorer total B-ECOHIS scores. Dental discoloration and untreated caries lesions had a negative impact on the OHRQoL in pediatric liver transplant candidates.